The effect of faunus ater shell as filler in asphalt concrete wearing course (AC-WC) mixtures - Firmansyah, Rachman; Tamalkhani, Syammaun; Putra Jaya, Ramadhansyah; R., Akmal (AIP Publishing, 2023)
In the composition of the asphalt mixture, the filler is vital to the aggregate skeleton. One of the filler functions is to increase the mixture’s stability and density by filling the void in a bigger aggregate. However, since the filler requirement needs to be smaller than 0.075 mm, it isn’t easy to collect enough quantity to fulfill the mixture requirement. Hence, this study aims to study the Faunus ater waste as filler in asphalt concrete wearing coarse (AC-WC) mixture, since it is a waste and has little economic value. This study incorporates Bina Marga’s specifications and following the standard Marshall testing method to investigate the effect of utilizing Faunus ater (FA) shell as filler. The result shows that the addition of Faunus ater shell in the mixture shows an increase in both stability and flow testing results. Thus, Faunus ater addition as filler may have a good impact on the pavement in terms of stability; however, it needs conservative treatment since the Marshall flow became high. It is not ideal for asphalt pavement.